2010
DOI: 10.1016/j.bbmt.2010.03.023
|View full text |Cite|
|
Sign up to set email alerts
|

Salivary Gland Involvement in Chronic Graft-Versus-Host Disease: Prevalence, Clinical Significance, and Recommendations for Evaluation

Abstract: Although xerostomia is a commonly reported complaint in patients with chronic graft versus host disease (cGVHD), criteria for evaluating the prevalence and characteristics of salivary gland involvement have not been well defined in this patient population. Prior studies also do not make distinction between salivary and mucosal oral cGVHD. We have systematically evaluated sicca symptoms and signs in a large cohort of patients with cGVHD (N=101) using instruments widely used to study Sjogren’s Syndrome. Xerostom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
121
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(132 citation statements)
references
References 28 publications
6
121
5
Order By: Relevance
“…Severe involvement of the MSG in cGVHD results in marked destruction of the secretory units and, thus, in permanent and profound oral dryness. 27,28 Unlike our results, Soares et al 14 found increased CD68 þ cell number in cGVHD patients, compared with non-cGVHD HSCT patients. This discrepancy might be explained by the previous development of acute GVHD.…”
Section: Discussioncontrasting
confidence: 56%
“…Severe involvement of the MSG in cGVHD results in marked destruction of the secretory units and, thus, in permanent and profound oral dryness. 27,28 Unlike our results, Soares et al 14 found increased CD68 þ cell number in cGVHD patients, compared with non-cGVHD HSCT patients. This discrepancy might be explained by the previous development of acute GVHD.…”
Section: Discussioncontrasting
confidence: 56%
“…Recent studies on HSCT recipients with GVHD have reported the prevalence of pathological Schirmer's scores of B70% during the observation periods of 6 months to 3 years. 11,39 The present study indicates that this complication has an irreversible nature and that conditioning regimen may have a major role, as past or present GVHD did not correlate with sicca symptoms nor with a pathological Schirmer's test. The impact of the conditioning regimen (TBI) in the development of other ocular late effects, such as cataracts, has been well described.…”
Section: Discussionmentioning
confidence: 86%
“…6,17 Moreover, general malnutrition and even vitamin A deficiency can be encountered, causing dehydration with oral and ophthalmological symptoms. 11,18,19 So far only a few studies have addressed the functional well-being of survivors after HSCT. In a retrospective multicenter analysis in patients surviving 5 years or more after HSCT, a Karnofsky score X90% was reported in 93% and only 6% of these patients did not return to school or work after HSCT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In graft-versus host disease (GVHD), salivary glands are one of the primary target organs besides skin and gastrointestinal tracts (Imanguli et al, 2010;Nagler et al, 2004), and impaired secretion of saliva affects patients' quality of life through oral filthiness, caries and decreased appetite. Although this symptom is well-known, pathophysiology and mechanism of salivary gland injury have been poorly investigated.…”
Section: Introductionmentioning
confidence: 99%